General Chart of Accounts and its Improvement - Vasilii Vasil’evich Shcherbatyuk (Учёт. Анализ. Аудит, 2019)
Introduction, Purpose. Accounts play a crucial role in modern accounting systems of all countries. They provide the most complete and reliable information both for generating financial statements and making the best educated management decisions. The new Moldovan General Chart of Accounts should help to achieve this goal, but it has significant shortcomings that adversely affect the quality and effectiveness of accounting and control processes, which underpins the relevance and practical importance of this article. Methods. The research was carried out by the author in the period from 2014 to 2017 using general scientific methods of cognition (comparison, analysis, synthesis, induction, deduction, abstraction, grouping, modeling, logical and system approaches), methods of special economic sciences (documentation, double entry, accounts, financial statements, etc.) and various sources of information (normative acts, national and foreign specialized academic literature). Results. The article gives a brief description of the accounts and reveals the cause-effect relationship between accounts and accounting objects. The author coins a new concept of “operational field” and interprets its meaning. The article describes in detail the distinctive features of the newly introduced General Chart of Accounts and compares it with similar normative acts of the Russian Federation, the Ukraine, the Republic of Belarus, Kazakhstan and Tajikistan. The author critically reviews the basic methodological provisions of the General Chart of Accounts, makes and justifies a number of proposals for its further development in the context of the transition to the International Financial Reporting Standards. Discussion. The results of the research supplement and develop the conclusions of other academics. In the long term it is recommended to develop and implement a General International Chart of Accounts across the world, but various factors of political, financial, organizational-methodical and methodological nature makes it difficult.